Estudo da hidrólise enzimática do amido de mandioquinha-salsa (Arracacia xanthorrhiza): efeito do tamanho dos grânulos - Rocha, Thaís de Souza [UNESP] (2007)
Enzymatic hydrolysis of granular starch has been used to study the structure and the physicochemical properties of the granules. It depends, among others, on the starch botanic source, on the enzymatic system used and on the size of the granules. The aim of this work was to investigate the effect of granule size on enzymatic susceptibility and on structural and physicochemical properties of Peruvian Carrot starch. Starches from two varieties (Amarela de Carandaí, AC and Amarela de Senador Amaral, ASA) were isoladed, fractionated by size and classified into whole granules (without separation); large granules (d 20æm); medium granules (> 10 e < 20æm) and small granules (£ 10æm). The whole and fractionated granular starches were hydrolysed with bacterial -amylase and fungal amyloglucosidase. Samples, before and after hydrolysis, were analyzed regarding their structural and physicochemical characteristics. The whole and fractionated native starches shown in optical microscope and scanning electron microscope circular shape for large granules and polygonal shape for small granules. The granular surface was smooth with some had openings, especially for the larges granules, with some depressions and holes. From chromatograms of gel permeation in Sepharose CL-2B was not possible to observe differences on the molecular size from both varieties of Peruvian Carrot. The amylose content, that was higher to AC variety, was concentraded mainly in large granules. Both varieties exhibited B-type X-ray diffraction pattern and relative degree of cristallinity (DC) (~20%) was not different for the different starches, despite the intensity of the peaks decrease for small granules. The intrinsic viscosity of starches from both varieties was smallest 24% and 14%, respectively, to small granules in relation of large granules. Gelatinization temperatures, from DSC, decreased as the granule sizes decreased, while the enthalpy remained the same. The smaller the granule